Analysis of Technical and Operational Requirements for Earth Stations in Motion in Ka-band - Ruiqing WEN; Jin JIN; Zhen HUANG (天地一体化信息网络)
Current technical and operational requirements for FSS GSO ESIM in Ka-band was in-depth researched.Referring to Radio Regulations and ITU recommendations, a model for theoretical calculation was established and restraining logic between each requirement and theory of depressing interference to adjacent satellites was analyzed.Then working conditions of NGSO ESIM in Ka-band was analyzed using the similar methods and the diff erences between GSO ESIM and NGSO ESIM and the infl uences on requirements of NGSO ESIM was illustrated.The results of this article provided some references for setting technical and operational requirements of NGSO ESIM.